2003
DOI: 10.1017/s1121189x00006187
|View full text |Cite
|
Sign up to set email alerts
|

Patient cues and medical interviewing in general practice: examples of the application of sequential analysis

Abstract: SUMMARYAims – To illustrate how sequence analysis may be applied to the medical interview to: 1. explore how physicians without formal training in communication skills elicit and respond to patient cues and expression of expectations and opinions; and 2. test the hypothesis that physicians' closed ended questions determine the use of subsequent closed ended questions. Methods – 238 consultations in primary care, coded with the Verona Medical Interview Classification System, were analysed. Lag 1 analysis was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…To date the majority of studies investigating the relationship between patient cue expression and provider response have adopted a ‘lag 1 sequential analysis’ approach [13,15,16]. While it is important to understand communication influences between adjacent utterances, the limitation of this approach is that the longer-term speech influences remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…To date the majority of studies investigating the relationship between patient cue expression and provider response have adopted a ‘lag 1 sequential analysis’ approach [13,15,16]. While it is important to understand communication influences between adjacent utterances, the limitation of this approach is that the longer-term speech influences remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on the concerns of clinical physicians has been extensive. Studies have found that attentive and respectful listening in communication reinforced the healing process and positively affected patient satisfaction;2123 theater training was effective at teaching clinical empathy;24 empathic responses during doctor–patient information exchanges were consistently associated with positive patient outcome, stable patient adherence, and symptom resolution;2530 a physician’s attention to a computer monitor diminished dialogue between the physician and the patient and was inversely correlated with the effect of communication;31 and audiovisual aids, such as figures, pictures, DVDs, and MP3 files, were helpful for transferring medical information, promoting doctor–patient communication, and improving patient comprehension, recall, and adherence 3235. To our knowledge, there have been few or no studies with regard to the effectiveness of a simulator or anatomic model in promoting doctor–patient communication and improving patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the topics of EACH committee members' most recent publications, new areas of interest include, for instance, the role of the broader context in which a problem is presented [11], unconventional outcome measures such as skin conductance and cortisol [12] and new interaction analysis systems, such as sequence analysis and cue-responding [13][14][15][16][17][18]. There also appears to be an increasing interest in the role of the nurse-patient communication [19,20] and role delineation [21,22] as well as a renewed interest in decision-making [23], breaking bad news [24,25], training effects [26][27][28] and somatization [29,30].…”
Section: Developments In Communication In Healthcarementioning
confidence: 99%